Impact of Gamification on Education Prime Time - Kainat Javed, Saima Rafique, Tayyaba Azhar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the effectiveness of Gamification approach for teaching anatomy to first year medical students by comparing the students’ performance in traditional teaching with gamification approach. Method: A Comparative Analytical study was conducted in undergraduate students having Taught anatomy in a private medical college of Lahore (mention Name), from 16th July -31st August 2019. A total 155 students of 1st year MBBS were enrolled and divided randomly into two groups Group 1(Traditional n=77) and Group 2 (Gamification n=78). Shapiro-wilk and Kolmogorov-smirnov test were applied to check the normal distribution of pre-test and post-test scores. Comparison of pre and post test scores by paired sample t-test resulted in significant decrease in the control group while a significant positive change in learning of experimental group. Results: Findings of the study showed that students studied in Group 2(i.e. Gamification) achieved the highest scores in post-test, compared with the other group. Mean difference of Group 2 is (MD=-6.100) compared to Group 1(Traditional) which is MD=-1.040 and paired sample t-test shows p-value=.000 of both groups, thus evident from the statistics that students of group 2(Gamification) achieved high scores as compared to traditional group. Conclusion: This study concluded that planned gamification frameworks can be generally welcomed by students. It is recommended that this approach in small group discussion is worth pursuing in future, this teaching approach can be implemented for teaching medical students where the role of teacher is more of facilitator.